Service Creativity In The Cultural Tourism Performing Arts’ Ecosystem - Scholastica Wahyu Pribadi (Economics and Business Journal (ECBIS), 2026)
Abstract also written in English containing key issues, objectives, methods and results. Abstract This study examines the role of service creativity in the performing arts ecosystem within the context of cultural tourism, highlighting how service processes contribute to value creation beyond the artistic aspect. Cultural tourism has shifted from an object-based orientation to an experiential one, understanding performing arts not merely as a creative product but as an experience constructed through interactions between service providers and consumers. In this context, service becomes an integral part of the value creation process and audience satisfaction. This research uses a qualitative approach with a single case study method at PT Mata Hati Kitapoleng, a performing arts company in Bali. Data collection was conducted through in-depth semi-structured interviews and non-participatory observation. This research focuses on how service creativity is built through organizational processes, interactions, and practices. The results show that service creativity is formed through a structured yet flexible process, which integrates empathy for consumers, team collaboration, idea exploration, and continuous evaluation. The design thinking approach enables companies to deeply understand consumer needs and translate them into personalized and meaningful experiences. Service in this context is understood as a co-creative process, where consumers play an active role in shaping the final outcome. Furthermore, consumer satisfaction is influenced by various factors, such as trust, production and financial efficiency, innovation capacity, and evaluation and feedback mechanisms. This research confirms that service creativity is a strategic element in enhancing the competitiveness and sustainability of performing arts businesses within the cultural tourism ecosystem.